DASAR PEMIKIRAN PEMBERIAN SIFAT FINAL DAN MENGIKAT DEWAN KEHORMATAN PENYELENGGARA PEMILU SEBAGAI LEMBAGA ETIK - I Gede Druvananda Abhiseka (Fakultas Hukum, Universitas Warmadewa, 2025)
This article aims to analyze the final and binding nature of the DKPP from a True Perspective (Nature). This research also aims to examine the final and binding nature of the DKPP l in building the personal integrity of public officials. This paper uses normative legal research methods with a statutory approach, a conceptual approach using techniques for searching legal materials using document studies and analyzing studies quantitatively. The research results show the perspective of the essence of DKPP, the aim of which is to create electoral justice and a democratic culture with integrity and credibility in election administration, and this is also in line with the perspective of building the personal integrity of public officials, which has an important role in maintaining the image of democracy, because as General election organizers must maintain personal integrity and institutional integrity, which is an important point for maintaining a culture of democracy and electoral justice, this is in line with what is stated in the IDEA principles is Independent, impartiality, integrity, transparancy. efficiency, professionalism and service-mindedness.